Humanistic Leadership for Organizational Learning Capability: Integration of Maqashid Syariah and Knowledge Management - Nurcahyo, Satria Avianda; Anis, Muhammad; Thoha, Anis Malik (International Journal Ihya' 'Ulum al-Din, 2024)
This research aims to explore the application of humanistic leadership within the Ministry of Religion, Semarang Regency, particularly in how it enhances organizational learning capability (OLC) through the perspectives of Maqasid Syariah and knowledge management.Humanistic leadership emphasizes human values, interpersonal relationships, and self-development within organizations. This study explores how humanistic leadership can improve OLC through the perspectives of Maqasid Syariah and knowledge management. Using a qualitative method with in-depth interviews, data was collected from employees regarding their perceptions and experiences with humanistic leadership, Maqasid Syariah principles, and knowledge management practices. Thematic analysis identified patterns in the application of these principles in the work environment. Findings indicate that humanistic leadership significantly fosters a work atmosphere conducive to learning and innovation. The incorporation of Maqasid Syariah values, like spiritual and intellectual well-being, supports an ethical and inclusive organizational culture. Additionally, effective knowledge management practices, such as documentation and knowledge sharing, reinforce OLC by motivating and engaging employees in continuous learning. This research underscores the importance of integrating humanistic leadership with Maqasid Syariah and knowledge management in organizational development strategies. The Ministry of Religion can leverage these findings to enhance employee performance and capability, promoting the achievement of organizational goals more sustainably.